2009
DOI: 10.1017/s0952675709001730
|View full text |Cite
|
Sign up to set email alerts
|

Learning lexical indexation

Abstract: Abstract. Morphological concatenation often triggers phonological processes. For instance, addition of the plural suffix /-ǝn/ to Dutch nouns causes vowel lengthening in some nouns due to the weight-to-stress principle ([xɑt] vs. [xáː.tǝn] 'hole'). These kinds of processes often apply only to a subset of words -not all Dutch nouns undergo this process ([kɑt] vs. [kɑ.tǝn] 'cat'). Nouns need to be lexically indexed as either undergoing this process or not. I investigate how phonological grammar and lexical ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 26 publications
2
34
0
Order By: Relevance
“…A long tradition of typological research has established strong universal patterns across languages, a result that could be interpreted as favoring a system that includes a strong Universal Grammar. Recent research in artificial grammar learning has also shown that linguistic patterns that counter such universal trends are either unlearnable or at least not easily learnable (Carpenter 2006(Carpenter , 2010Coetzee 2009b;Moreton 2008;Pater and Tessier 2006). On the other hand, there are also unambiguous examples of languages with grammars that counter universal trends (Coetzee and Pretorius 2010;Hyman 2001), showing that it should be possible for language learners to acquire grammars that do not fit neatly into the limits of Universal Grammar.…”
Section: 1mentioning
confidence: 99%
“…A long tradition of typological research has established strong universal patterns across languages, a result that could be interpreted as favoring a system that includes a strong Universal Grammar. Recent research in artificial grammar learning has also shown that linguistic patterns that counter such universal trends are either unlearnable or at least not easily learnable (Carpenter 2006(Carpenter , 2010Coetzee 2009b;Moreton 2008;Pater and Tessier 2006). On the other hand, there are also unambiguous examples of languages with grammars that counter universal trends (Coetzee and Pretorius 2010;Hyman 2001), showing that it should be possible for language learners to acquire grammars that do not fit neatly into the limits of Universal Grammar.…”
Section: 1mentioning
confidence: 99%
“…One straightforward and uninteresting possibility is random guessing; this predicts that speakers should simply assign equal probability to all possible patterns. Alternatively, speakers might choose the response that best satisfies paradigm uniformity constraints (Kenstowicz 1995(Kenstowicz , 1996Benua 1997;Steriade 2000;Coetzee 2009). If speakers were found to mirror lexical statistics in the forward direction, while employing random guessing or favoring uniformity only in the backward formation direction, this would also support an asymmetrical model such as the single base hypothesis.…”
Section: Single Base Hypothesis and Backward Formationmentioning
confidence: 99%
“…Surgery on ℜ works in tandem with standard ranking algorithms, like recursive constraint demotion (Tesar 2004), to learn exceptions (see Alderete (2008) for an illustration). Alternative conceptions of learning exceptions, like the Constraint Coindexing models of Pater (2009a) and Coetzee (2009), do not have a parsimonious relationship with OT learning protocols because they introduce a constraint selection problem. 6 Constraint Coindexing learns exceptional patterns by cloning constraints (either markedness or faithfulness constraints) and then associating them with specific material of the lexical entry via an index.…”
Section: Encoding Multiple Patterns In the Same Grammarmentioning
confidence: 99%